Perspektif Hukum Pidana Serta Penegakannya Terhadap Tindak Pidana Perjudian Sabung Ayam Di Kabupaten Pohuwato - Nurulfadillah Nurul (Indonesian Civil Law Review, 2025)
Gambling crimes, including cockfighting, are a complex issue in Indonesia's criminal law. In Pohuwato Regency, this practice has become a social phenomenon involving many individuals, despite being contrary to existing laws. This study aims to analyze the criminal law perspective and the law enforcement mechanisms against cockfighting gambling crimes in the region. This research employs an empirical juridical method with a qualitative approach. Data were obtained from the Pohuwato Police Criminal Investigation Unit (Reskrim Polres Pohuwato) in 2024 and other relevant sources. A descriptive analysis was conducted to illustrate the legal aspects, social impacts, and law enforcement efforts that have been implemented. The findings indicate that despite various law enforcement efforts, cockfighting gambling remains widespread. The main obstacles to enforcement include weak regulations, limited resources, and social tolerance toward gambling. Additionally, the involvement of various parties in gambling networks further complicates enforcement efforts. This study concludes that a more effective and comprehensive approach is needed to enforce the law against cockfighting gambling. The proposed recommendations include strengthening regulations, enhancing the capacity of law enforcement officers, and educating the public to reduce gambling practices in Pohuwato Regency. With these measures, it is expected that law enforcement can be more effective and serve as a deterrent for offenders.